2013
DOI: 10.1371/journal.pgen.1003806
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Systematic Analysis Reveals Different and Predictive Proliferation Expression Signatures of Cancerous vs. Non-Cancerous Cells

Abstract: Understanding cell proliferation mechanisms has been a long-lasting goal of the scientific community and specifically of cancer researchers. Previous genome-scale studies of cancer proliferation determinants have mainly relied on knockdown screens aimed to gauge their effects on cancer growth. This powerful approach has several limitations such as off-target effects, partial knockdown, and masking effects due to functional backups. Here we employ a complementary approach and assign each gene a cancer Prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Although several pioneer studies identified genes periodically expressed during different phases of the cell cycle (4, 5), limited progress has been made regarding the identification of genes with differential expression patterns in tumors with high and low proliferation rates (7,8). Consistent with previous studies using a small number of cancer lines from nine different tumor types (NCI60 set containing 7 colon cancer cell lines; refs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although several pioneer studies identified genes periodically expressed during different phases of the cell cycle (4, 5), limited progress has been made regarding the identification of genes with differential expression patterns in tumors with high and low proliferation rates (7,8). Consistent with previous studies using a small number of cancer lines from nine different tumor types (NCI60 set containing 7 colon cancer cell lines; refs.…”
Section: Discussionmentioning
confidence: 85%
“…Because a major hallmark of cancer is uncontrolled rapid proliferation, it was not surprising to find that many of the genes that control cellcycle progression were deregulated in the different tumor types investigated, compared with the corresponding normal tissue (4,6). However, despite some early studies (7,8), the genes with higher expression in rapidly proliferating tumor cells compared with slowly cycling tumors are not as well characterized. This is of considerable clinical relevance because it has been repeatedly observed that rapid tumor proliferation is associated with poor patient prognosis (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The genes included in the networks are significantly overexpressed both in normal tissues and especially in cancers (Wilcoxon rank sum p values <6.29 3 10 À8 ). Interestingly, the network genes are significantly associated with cancer proliferation and less associated with normal proliferation (Waldman et al, 2013). They are highly enriched with human orthologs of mouse essential genes (hypergeometric p values <1 3 10 À30 ) and are evolutionary conserved (Wilcoxon rank sum p values <2.99 3 10 À17 ).…”
Section: Evaluating Daisy Based On Experimentally Detected Sl Interacmentioning
confidence: 99%
“…Several studies have highlighted the specific participation of ribosomal proteins, sets of microRNAs, and spliceosomes in translation and concomitant proliferation [47]. Additional research studied the gene signature of 60 cancer cell lines and concluded that protein translation is inseparable from the proliferative phenotype [47]. Topical results summarized the significant role of translational apparatus in cancer promotion and progression [48].…”
Section: Discussionmentioning
confidence: 99%